Penerapan Nilai Keadilan dalam Bidang-bidang Utama Kehidupan Masyarakat Bertamadun: Analisis Menurut Perspektif Al-Quran - Brahim @ Ibrahim, Ahmad Zaki (Jurnal Usuluddin, 2004)
This article tries to elaborate the concept ofjustice in Islam and its application in the major fields of civilized society based on Quranic perspective. By examining the verses of al-Qur an and the practice of al-sahabah and Muslim leaders in Islamic history, it concludes that Islam has its own interpretation of justice as has been practiced in Muslim society especially in the time of Prophet and his companions. The significant of practicing this value by man as vicegerent of God in this world i.e. in legislative, excecutive and judicative and other fields of life will be expounded in this article.